Early Detection of Neonatal Cholestasis: Inadequate Assessment of Stool Color by Parents and Primary Healthcare Doctors - Witt, Mauri; Lindeboom, Jeanet; Wijnja, Corry; Kesler, Anneke; Keyzer-Dekker, Claudia M. G.; Verkade, Henkjan J.; Hulscher, Jan B. F. (European Journal of Pediatric Surgery, 2016)
Introduction Early diagnosis and surgery (< 60 days of age) improve outcomes in children with biliary atresia. Only 56% of patients undergo timely surgery in the Netherlands. Lack of acquaintance with symptoms such as discolored stools might underlie this delay. We analyzed whether Dutch parents, youth healthcare doctors, or general practitioners recognized discolored stools and evaluated the effect of the Infant Stool Color Card (ISCC) on recognizing discolored stools.Material and Methods We asked 100 parents, 33 youth healthcare doctors, and 50 general practitioners to classify photographs of stools as “normal” or “abnormal.” Subsequently, we asked whether parents would seek medical help and doctors would refer the patient for medical investigation. Finally, parents scored stools using the ISCC.Results Two-third of both parents and youth healthcare doctors recognized all discolored stools. Only half of them would seek medical help for all discolored stools resp. refer patient for medical investigation. Only one-third of the general practitioners recognized all discolored stools and would refer for medical investigation for all discolored stools. Using the ISCC, the percentage of parents recognizing all discolored stool increased from 66 to 87% (p < 0.01).Conclusion Neither parents nor youth healthcare doctors nor general practitioners reliably recognize discolored stool. The ISCC is an effective screening method for discolored stool. Our data indicate that the ISCC should be accompanied by unequivocal advices regarding referral for medical investigation upon detection of discolored stools.
Keywords: neonatal cholestasis; biliary atresia; Infant Stool Color Card; discolored; stools